A Flexible and Reliable Traffic Control Protocol for Wireless Multimedia Sensor Networks. (27th April 2014) - Wang, Zhiqi; Yu, Fengqi
Wireless multimedia sensor networks (WMSNs) are more and more wildly used for a variety of applications nowadays. The quality-of-service (QoS), as a measure of system performance, is very important and attracts many researchers. The limited bandwidth should be adjusted for the packets with different priorities precisely. Even more, when the WMSNs are used for environment monitoring, besides the real-time video playing, the monitoring systems also need to record and playback the video after some time. So the necessary and proper retransmission should be added to the real-time video transmission, without affecting the normal data streams. To emphasize the problem, the paper provides a flexible and reliable traffic control protocol. According to the packet priorities, sensor nodes in one collision area can adjust their sending states adaptively. Variable retransmission tactics are provided for the packets with different priorities. The simulations show that the bandwidth adjustment can protect the packets with high priority effectively, and the performance of the retransmission is well positioned to meet the requirement of the multimedia applications.